Effect of solvent composition on the formation of hydroxyapatite/ silk fibroin composites prepared using sol-gel method - Suchaya Sriudom (2018)
Hydroxyapatite (HA) has been widely utilized in the biomedical applications due to its chemical and structural features that are similar to the natural bones. The addition of organic components enhances the flexibility of the HA-based composites which result in increasing its molding ability into any desirable shapes. In this article, preparation of hydroxyapaptite/silk fibroin (HA/SF) composite using sol-gel method is reported. The optimal condition for preparing the HA/SF composites was determined by judging from their crystallite size, crystallinity and particle size distribution, morphology and calcium/phosphorus (Ca/P) ratio investigated with X-ray diffraction analysis, particle size analyzer, scanning electron microscopy and energy dispersive Xray spectroscopy, respectively. The HA/SF composite was successfully prepared in the binary solvent of ethanol and water at the optimal volume ratio of 4:1. At this solvent condition, the composites had a uniform rod-liked shape, ranging from 30-70 nanometers. The Ca/P ratios of all composites are close to the theoretical value of about 1.67. © (2014) Trans Tech Publications, Switzerland.